PENGARUH HARGA DAN FASILITAS TERHADAP KEPUASAN KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PERUMAHAN PONDOK PERMATA SUCI GRESIK - ELLA ISDA ALFA SETIA DIATY (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This study aims to determine the direct and indirect effects of prices and facilities on decision makers and customer satisfaction in the Pondok Permata Suci housing in Gresik. The research data was obtained from the distribution of questionnaires to 100 respondents who bought and resided in PSS using proportional sampling techniques. Tests are carried out using path analysis techniques. The results showed that prices and facilities have a direct effect on purchasing decisions, purchasing decisions have a direct effect on consumer satisfaction, prices and facilities have a direct effect on consumer satisfaction, and prices and facilities have an indirect effect on customer satisfaction through purchasing decisions